Inspired by nature: an engineering design-based biomimicry activity. (3rd April 2021) - Canbazoğlu Bilici, Sedef; Küpeli, Mehmet Ali; Guzey, S. Selcen
Abstract: This activity provides opportunities for middle school students to design bio-inspired, eco-friendly vehicles. Twenty-four 8th grade students (12 girls, 12 boys) engaged in the activity which was implemented in four class periods, 40 minutes each, in an elective Environmental Education course. During the activity, students engaged in engineering design process and they integrated eco-friendly systems that can be used to solve the problem of air pollution. In this process, the students researched and observed living organisms and made their designs inspired by the body and movement systems of grasshoppers, ants, spiders and red Japanese beetles, and added eco-friendly elements (such as solar panels, exhaust filtering systems, hybrid batteries, electric motors) to their prototype vehicles. Working as "engineers", students had the opportunity to gain knowledge and engage in engineering design practices. The activity helped students explore science concepts such as biomimicry, air pollution, and structural features of different living organisms. This study suggests the use of biomimicry design activities in STEM classrooms.